Immune response profiles after caterpillar exposure: a case report - Tamar A Smith-Norowitz; Kevin B Norowitz; Stephan Kohlhoff; et al (Dove Medical Press, 2010)
Tamar A Smith-Norowitz1,3, Kevin B Norowitz1, Stephan Kohlhoff1,3, Kaushal Kalra1,3, Seto Chice2,3, Martin H Bluth41Departments of Pediatrics, 2Pathology, 3Center for Allergy and Asthma Research, SUNY Downstate Medical Center, NY, USA; 4Department of Pathology, Wayne State University School of Medicine, Detroit, MI, USARationale: The role of the immune response to caterpillar exposure is not well described. This case study is the first to report a patient who presented with an allergic reaction after exposure to the larvae of the sycamore tussock moth, Halysidota harrisii Walsh, 1864.Methods: Blood was collected from an allergic asthmatic adult (m/42 y/o) at 2 hrs – 2 wks after contact urticaria with associated dyspnea after exposure to the larvae of the sycamore tussock moth, Halysidota harrisii Walsh, 1864. Distributions of blood lymphocytes (CD4+, CD8+, CD8+CD60+, CD19+, CD23+, CD16/56+, CD25, CD45RA+, CD45RO+), monocytes (CD1d+), levels of serum immunoglobulins (IgM, IgG, IgA, IgE), and cytokines (IFN-γ, IL-4, TNF-a) were studied (flow cytometry, nephelometry, UniCAP Total IgE Fluoroenzymeimmunoassay, cytokine ELISA, clinical toxicology).Results: Numbers of CD4+ T cells, CD25+ cells, CD19+ B cells, and CD1d+ monocytes decreased (22, 27, 33, 20%, respectively) one week post reaction, CD45RA+ naïve T cells decreased at 36 hours (21%),while CD8+CD60+ T cells and CD23+ cells decreased 48 hrs (33, 74%, respectively) post reaction. In contrast, numbers of CD16/56+ NK precursor cells increased (60%) 12 hrs, then decreased (65%) 48 hrs post reaction; other lymphocyte subsets were unaffected. Serum IgM, IgG and IgA were within normal range; however, serum IgE demonstrated a bimodal elevation at 2 hrs (15%) and one week post reaction. Levels of IFN-γ, IL-4, and TNF-a were not detected in serum pre-exposure (<1.0–4.0 pg/mL). However, high levels of IFN-γ (187–319 pg/mL) and TNF-a (549–749 pg/mL) were detected in serum 24–36 hrs and 3.5–24 hrs post reaction, respectively. In contrast, levels of IL-4 were undetected (<1.0 pg/mL) in serum at all time points.Conclusions: Exposure to the larvae of the sycamore tussock moth, Halysidota harrisii Walsh, 1864 may result in increased cytokine levels and blood CD16/56+ NK precursor cells.Keywords: caterpillar exposure, Halysidota harrisii Walsh, 1864, serum IgE